Peace and conflict resolution: Biafra agitation and zoning of presidency in Nigeria - Yerima, Hindatu Maigari; Ibrahim, Muhammad Bello; Terwase, Isaac Terungwa; Abdul Talib, Asmat Nizam (International Institute for Science, Technology and Education (IISTE), 2016)
The Nigerian State over the years, experienced continuous attacks from the Boko Haram insurgent group since the period of 2009 to date and that has affected the country’s national security. These continuous attacks have claimed the lives of so many Nigerians and its spread to other countries such as Chad, Niger and Cameroon, and have thus, called for the attention of the international community.Tracing the root causes of the insurgency, similar approach reveals for the new call for Biafra’s secession from Nigeria in 2015. This research paper seeks to investigate the role of zoning and rotation of presidency between the Nigeria’s six geo-political zones as a panacea for resolving the conflict between the North and South, as well as ethno-religious conflicts that bedeviled the peaceful co-existence of the Nigerian State which has the largest population in Africa.The research paper made use of qualitative approach through the conduct of interviews, review from previous literature, online newspapers and other internet sources as means of data collection. The findings, thus, reveal that the Igbo ethnic nationality from the South-East geopolitical zone foresee no hope of occupying the seat of the President of Nigeria hence, the need for secession from Nigeria in order to achieve self-determination through the Republic of Biafra which was fought for in 1967-1970 during Nigeria’s civil war.